Evaluación de una cerveza artesanal tipo ale a base de frutos secos con una base de malta de caramelo con un banco de 10 litros. (2021)
This document presents the initiative to create the beer entrepreneurship initiative artisanal; a beer with a unique flavor, with which people can experience different sensations on the palate and that in turn can be a competitive product against the great demand for beers and spirits in the city of Bogotá.From the above you have as a main objective to evaluate the craft beer type ale based on nuts (almonds) with a caramel malt; which meets the required factors that guarantee a premium quality product, and therefore also be a competitive product within the market, which generates a transcendence in the consumer. It should be noted that for completing the process of craft brewing, the variables were taken into account of process of greater impact, which were: the temperature, the pH, degrees Brix, the IBU and the density; on the other hand, the extract of the almonds was selected for the elaboration of the beer and the cost of production was established, taking into account labor, the equipment and raw materials; to complete, a technical and detailed diagnosis of the final product, obtaining a product with quality standards in accordance with the references theoretical according to the style and microbiological load.